Elder Victimization and Routine Activities: An Examination of the Predictors of Fraud and Burglary for those Age 60 and Older - Tapp, Susannah Naomi (2018)
As the elderly population continues to grow, the victimization of the elderly becomes an increasingly important topic. While there is a great deal of research on victimization, most of that research has focused on young adults, those who commit the majority of crimes. What research on the elderly and crime does exist has focused on either fear of crime or elder abuse. The criminal victimization of the elderly is not considered. The current study tested the applicability of routine activities lifestyles theory to the criminal victimization of the elderly for two crimes: burglary and fraud. Using multiple waves of data from the Health and Retirement Study, the roles of target vulnerability, exposure to motivated offenders, presence of guardians, and engaging in risky behavior on criminal victimization were examined. A series of binary logistic regressions were run to test the impact of these factors. Additionally, two subsamples, looking at family related factors, were examined. The study found that findings based on studies of younger individuals that prior victimization is one of the strongest predictors of victimization could be applied to the elderly. Most individuals age out of crime and victimization, but others who do not. Additionally, being Hispanic, having financial difficulties, and, in some cases, relationship quality and problems with family members also influenced the odds of victimization